المستخلص تمثل إدارة التغيير التنظيمي، نهج يُتبع لتحويل او انتقال الفرد، او فريق العمل، او المنظمة من حالة راهنة الى حالة مستقبلية مخطط لها. فهي عملية تنظيمية تهدف إلى مساعدة اصحاب المصلحة للقبول ومن ثم تبني التغييرات في بيئة الاعمال الخاصة بهم. ويمكن - الجبوري حمزة محمد (Journal of Economics and Administrative Sciences, 2016)
The organizational change management, follows the approach to the transfer or transmission of the individual, or team, or the organization of the current case to the case of a future planned. It is an organizational process aimed at helping stakeholders to accept and then the changes in their business environment. And job satisfaction can be defined as the individual’s sense of happiness and satisfaction during the performance of his work and achieved compatibility between what the individual expects from his work and how much it actually gets in this work, and job satisfaction is to pay the individual components of the work and production. Through the concepts above chose researcher on the title search goal of: "The impact organizational change management in job satisfaction among employees in orginization", in order to stand at the level of the relationship and the type of influence and power between the two variables mentioned, through test hypotheses two main which were submitted in the research methodology. Were distributed to identify search sample consisted of thirty (30) members of the individuals working in the Baghdad plant (tents)/ Baghdad- Waziriyah, in order to obtain the necessary data that was used later in the process of statistical analysis, where the research found the most important conclusion represented by the presence of a high level of correlation between the organizational change management and variables on the one hand, and job satisfaction among employees and variables on the other hand, as well as check the level of impact is acceptable between the organizational change management and variables of party, in job satisfaction among employees and variables at the opposite end, and this is what indicated by the results of the statistical analysis as for the most important research came out of recommendations represent intensify and encourage "interest organizational change management mechanisms followed in Baghdad plant (tents)/ Baghdad- Waziriyah, because of its positive effects on job satisfaction among employees".